IMPROVEMENT OF SKILLS IN WRITING EXPOSITORY TEXTS USING THE GROUP INVESTIGATION MODEL STUDENTS OF CLASS X SMKN 1 KINALI SCHOOL YEAR 2021/2022 - Rini Yusrita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
Based on the results of the initial observations made, it is known that the exposition text writing skills of class X students of SMKN 1 Kinali are still low. This is caused by three things, namely first, students are less enthusiastic in participating in the exposition text learning process. Second, students have difficulty in finding topics and arguments that will be written in the exposition. Third, students also have difficulty in pouring arguments into exposition text. the purpose of (a) Describing the learning process of writing exposition text through group investigation model in class X DKV 2 students of SMKN 1 Kinali, (b) Describing the improvement of exposition text writing skills in learning to write exposition text through group investigation model in class X DKV students of SMKN 1 Kinali. (c) Describing changes in students' behavior in learning to write exposition text through group investigation model in class X DKV students of SMKN 1 Kinali. This research is a classroom action research that uses the Group Investigation model as an effort to improve exposition text writing skills at X SMKN 1 Kinali. The variables of this research are exposition text writing skills and the use of group investigation model. The research instruments are test instruments and non-test instruments. Data collection techniques used test and non-test techniques. Data analysis was done quantitatively and qualitatively.